Analisis Semiotika Karikatur Konferensi Tingkat Tinggi Asean Ke 24 Pada Postingan Akun Instagram Jokowi - Syaputra, Andhika; Santoso, Puji (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
A caricature illustration is a visual work that is representative and symbolic, the main power of caricature lies in the idea of presenting a sign as a representation of a social and political event, without any illustration Readers can have different understandings of writing. Objective This research is to analyze the meaning of the signs behind Instagram posts Jokowi related to the caricature of the 42nd ASEAN Summit used by researchers for this research carried out since July 2023. This research was conducted on Jokowi's Instagram posts, regarding caricatures 42nd ASEAN Summit. Data collection techniques researchers used in this research is documentation. Data analysis This research was carried out using Charles Sanders' semiotic model Peirce which consists of three categories, namely sign, object and interpretant. The results obtained from researchers is that the signs in the caricatures are leaders ASEAN and related to the activities of the 42nd ASEAN Summit which was held in Labuan Bajo, East Nusa Tenggara, the object presented in the caricature of Jokowi it relates to activities that take place inside 42nd ASEAN Summit. Interpretant shown in 1 caricature unit includes various elements such as ASEAN Leaders, Dancers, Ship, ASEAN 2023 Logo, Komodo, Mountain, Sea, Fish, Orange Cat, Cat gray, as well as someone swimming.